THE INFLUENCE OF HEDONIC SHOPPING MOTIVATION AND ELECTRONIC WORD OF MOUTH INFORMATION ON ONLINE IMPULSIVE PURCHASING OF ISLAMIC FASHION PRODUCTS - Nugraha, Jeffry (Journal of Business Management Education (JBME), 2024)
Impulse buying is the act of purchasing a product or service suddenly without prior planning or in-depth consideration. These actions are usually triggered by emotional or visual stimuli, such as eye-catching advertising, big discounts, or strategic product placement in the store. Impulse buying often occurs when a person feels a strong urge to own something that catches their attention at that moment, without considering their true needs or the financial impact of the purchase. This research was conducted with the aim of understanding the influence of Hedonic Shopping Motivation and word of mouth on impulsive purchases of Islamic fashion products in Tasikmalaya City. The population in this study was 100 young women living in Tasikmalaya City. The results of this research show that Hedonic Shopping Motivation and Word of Mouth have an influence on impulsive buying. The results of the multiple regression analysis test show that Hedonic Shopping Motivation and Word of Mouth together have an influence of 48.9% on impulsive buying among young women in Tasikmalaya